Analisis Strategi Pemasaran Bakso Barupi ( Bakso Rusa Sapi ) Di Desa Burni Bius Kecamatan Silih Nara Kabupaten Aceh Tengah - fitri, ilma (Biram Samtani Sains, 2025)
Meatball traders are one of the businesses engaged in fast food processing. This meatball business has been around for a long time and has developed in rural areas in several sub-districts in Central Aceh Regency, one of which is in Silih Nara District. This meatball business has been able to survive since 2019 until now. This Barupi meatball stall (beef deer meatballs) is in great demand by local residents, even its customers have spread to Takengon City, even its customers come from outside Bener Meriah Regency, Bireuen and others. The purpose of this study is to "find out the marketing strategy, what marketing strategy is dominantly used, and to find out the impact of implementing the marketing strategy". The hypothesis of this study is that the strategy used in Marketing Micro, Small and Medium Enterprises of Barupi Meatballs (Beef Deer Meatballs) in Bius Village, Silih Nara District, Central Aceh Regency is a defensive strategy, namely a survival strategy. The data analysis method used in this study is the analysis tool used in this study consists of External Factor Evaluation (EFE Matrix) and Internal Factor Evaluation (IFE Matrix), External Internal Matrix (IE Matrix), SWOT Matrix (Strengths Weakness Opportunities Threats), and QSP Matrix (Quantitative Strategies Planning). The results of the study show that where internal factors include Strengths and Weaknesses where in this internal factor the Strengths position has a greater value weight when compared to the Weaknesses value weight. Namely, the internal factor in the Strengths position has a value weight of, namely (1.64) and Weaknesses of (1.00). External factors include Opportunities and Threats with a value weight of Opportunities of (23.93) and in the Threats position has a value weight of (12.30), so the position of Warung Barupi's business can be said to be quite good, because the Strengths and Opportunities positions have a higher value weight when compared to Based on the Threats and Weaknesses value weight. The marketing strategy position of micro, small and medium enterprises of bakso barupi (deer beef meatballs) in Bius Village, Silih Nara District, Central Aceh Regency is obtained. is in quadrant 1, namely an aggressive strategy, formed by a positive vertical axis (opportunities and threats) and intersecting with a positive horizontal axis (strengths and weaknesses)